An experimental study of the dynamics of the reaction H+CO2 -> OH(v ',j ',f)+CO: Product state-resolved differential cross sections and translational energy release distributions - Brouard, M; Hughes, D; Kalogerakis, K; Simons, J (1998)
Angular distributions and pair-correlated translational energy distributions have been measured for OH(v′ = O, N′ = 1), produced through the reactive scattering of hot H atoms by CO2 at 300 K and mean collision energies of 1.8 eV and 2.5 eV. The new measurements, together with those reported previously for the OH(v′ = 0, N′ = 5, A′/A″) products of the reaction at 2.5 eV, reveal that the differential cross sections depend strongly on collision energy and product quantum state. For the OH(v′/ = 0, N′ = 1) channel, the angular distribution changes from broad forward scattering to pronounced backward scattering as the collision energy is raised from 1.8 to 2.5 eV. The angular distributions at the higher collision energy shift from being backward to nearly isotropic, with forward-backward peaks, as the OH angular momentum is increased from N′ = 1 to N′ = 5. Although somewhat less dramatic changes are evident in the pair-correlated kinetic energy release data, the measurements confirm that the CO internal energy distributions are considerably colder than those predicted by statistical phase space theory. The results are discussed in light of earlier theoretical and experimental studies, particularly the results of femtochemical kinetic measurements.